2010
DOI: 10.1177/105268461002000504
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Physical and Social Environment of School: A Question of Equity

Abstract: This study explored the interplay between quality facilities and school climate, charting the effects of facility conditions on student and teacher attitudes, behaviors, and performance within schools slated for renovations in a large metropolitan school district. The research applied a school leadership-building design model to explore how six characteristics of facility quality-movement, aesthetics, play of light, flexible and responsive classrooms, elbow room, and security-interact with four aspects of scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
2
16
0
3
Order By: Relevance
“…Tanner [21] noted that classroom spaces arranged to promote freedom of movement were related to higher test scores. Another study by Uline et al [22] examined the effect of facility conditions on the overall learning climate for a large, metropolitan high school. The findings showed that physical conditions of the school played a role in shaping student behavior and performance.…”
Section: Hypothesis 1: When Seating Is Randomly Assigned Students Whmentioning
confidence: 99%
“…Tanner [21] noted that classroom spaces arranged to promote freedom of movement were related to higher test scores. Another study by Uline et al [22] examined the effect of facility conditions on the overall learning climate for a large, metropolitan high school. The findings showed that physical conditions of the school played a role in shaping student behavior and performance.…”
Section: Hypothesis 1: When Seating Is Randomly Assigned Students Whmentioning
confidence: 99%
“…Quando a estrutura escolar tem qualidade inferior ou é mal mantida, os alunos apresentam maior dificuldade em manter o foco, de modo que o ambiente desencoraja o engajamento deles nas atividades escolares, dificulta o processo de sustentação da atenção e ainda diminui o entusiasmo dos professores por seu trabalho (ULINE et al, 2010). O ambiente construído, então, não pode ser entendido como um mero invólucro onde acontecem as atividades educativas, mas sim como um agente impulsionador e motivador para a atividade, uma vez que interfere ativamente nos processos atencionais dos alunos.…”
Section: Fatores Ambientais Atenção E Aprendizadounclassified
“…A recurring line of research takes up the foundational questions of whether school facilities affect student outcomes like achievements, and thus, whether they warrant significant investment (Bowers & Urick, 2011;Cellini, Ferreira, & Rothstein, 2010;Oakes, 2004;Uline, 1997;Uline, Wolsey, Tschannen-Moran, & Lin, 2010). Davis (2015) noted that the most emphasized dependent variable is student test scores, though "researchers have also looked at the wider macro-social impact of high-quality school facilities on housing prices (Cellini, Ferreira, & Rothstein, 2010) and voters' support for schools" (p. 6).…”
Section: Research On the Effects Of Facilities On Educational Outcomesmentioning
confidence: 99%